Wartości istotne w procesie edukacji wczesnoszkolnej. Opinie studentów pedagogiki Uniwersytetu w Białymstoku - Dakowicz, Lidia Aldona; Laskowska, Agnieszka Dominika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article discusses the opinions of the surveyed students of pedagogy at the University of Białystok on the values that are important in the process of early childhood education. It deals with the issues related to the values which, according to the respondents, are important in the process of early childhood education, which values the respondents intend to transmit to their students in the future, and whether the respondents intend to transmit in the future those values which, in their opinion, are important in the process of early childhood education. The study involved 84 second-year full-time and part-time second-year undergraduate students of early childhood pedagogy. The research material was collected by means of the author's questionnaire. The analysis carried out allowed to establish that in the opinion of the students the most important values in the process of upbringing are being a good person and striving for knowledge, which is consistent with the values that the respondents intend to pass on to their students in the future. It is important for future teachers who play an important role in shaping the young generation to be aware that school is not only a place of transmitting information about the world, but also has an educational function.